Library book borrowing system using fingerprint technology / Faisal Abdullah - Abdullah, Faisal (2008)
Biometric is a technology that identifies a person based on physiology or behavioral characteristics. Nowadays, authentication systems using biometric technology have become more prevalent because of the advantages over password-based authentication systems. One of biometric methods is fingerprint authentication where it provides reliability and accuracy in the process of identify and verifying a person identity. Biometric authentication systems based-on this models provide high security for access control environment. The system presented in this paper called "Library Book Borrowing System Using Fingerprint Technology". It is developed based on biometric technology which using fingerprint capturing. Through this system, the researchers try to solve the better solution to change the barcode scanning to fingerprint verification in identifying the library system user. Some suggestion such as adding new features, interface improvement, and using the compatible fingerprint device were being discussed and to get a better result with more perfection that can be improved in future work compared to the current result which had been retrieved in this project.